‘Rowdy…? That’s the Whole Point of Going on a Night Out’: Time Out, Transgression and Control - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
As the previous chapter has highlighted, alcohol consumption plays an important role in the maintenance of friendships and in the individual and collective production of ‘girly’ or feminine identities in the NTE. Yet long-standing and pervasive images of alcohol consumption as a threat to femininity mean women’s negotiations of drinking continue to be fraught with tensions and ambivalences. In something of a paradox, ‘the contradictions engendered by post-feminist discourse constitute drunkenness as unfeminine, [yet] young women are enthusiastically exhorted to consume within the neoliberal culture of intoxication’ (Hutton et al. 2016: 82). In other words, to be a good, neoliberal citizen within leisure sites such as the NTE requires women to consume alcohol, yet the demands of femininity necessitate that they also show restraint. At the same time, the NTE is portrayed as a site where abandonment, hedonism and ‘rowdy’ behaviour are to an extent normalised, perhaps even encouraged, yet such behaviour ruptures traditional expectations of femininity as passive and ‘ladylike’. How do women negotiate and make sense of some of these tensions as they confront the ‘orderly disorder’ (Smith 2014: 2) of a typical night out? Is there a degree of acceptance of ‘rowdy’ or transgressive behaviour? And how does this sit alongside an expectation to be girly, as outlined in the previous chapter?
Keywords: Drinking Practices; Drunk Woman; Girly Girl; Kirsty; Transgressive Behavior